2004
DOI: 10.1023/b:chro.0000045802.75199.a6
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive search for chicken W chromosome-linked genes expressed in early female embryos from the female-minus-male subtracted cDNA macroarray

Abstract: In order to seek chicken W chromosome-linked genes expressed significantly earlier than the time of gonadal differentiation, female-minus-male-subtracted cDNA macroarrays were prepared from day 2 (Hamburger-Hamilton stages 12-13), day 3 (stages 19-20) and day 4 (stages 24-25) embryos. From a total of 15-744 macroarrayed cDNA clones, 610 clones exhibiting significantly female-specific expression were selected. When each one of the 610 cDNA clones was used as a probe in Southern blot hybridization with male or f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 26 publications
1
28
0
Order By: Relevance
“…The highest level of HINTZ expression was noted in males at the HH40 stage (post-differentiation) and decreased in gonadal adult tissues of both sexes ( Figure 3B). Previous studies (Yamada et al, 2004) and our results showed low HINTW expression in gonadal regions, during the HH20, HH25, and HH28 stages ( Figure 3C). We describe here for the first time that HINTW expression in female gonads peaked at HH35.…”
Section: Discussionsupporting
confidence: 81%
“…The highest level of HINTZ expression was noted in males at the HH40 stage (post-differentiation) and decreased in gonadal adult tissues of both sexes ( Figure 3B). Previous studies (Yamada et al, 2004) and our results showed low HINTW expression in gonadal regions, during the HH20, HH25, and HH28 stages ( Figure 3C). We describe here for the first time that HINTW expression in female gonads peaked at HH35.…”
Section: Discussionsupporting
confidence: 81%
“…Expression is detectable as early as day 2.5 (Yamada et al, 2004), and it persists in the developing urogenital system, nervous system, somites and limbs. In the embryonic gonads, the gene is expressed at all stages that have been examined, from the time of gonadal formation (day 3), throughout sexual differentiation (from day 6), and up to hatching (Hori et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…To avoid confusion, these sex chromosomes are deniminated Z and W. Thus in birds, snakes, and butterflies, for example, females have ZW sex chromosomes, and males have ZZ A c c e p t e d m a n u s c r i p t sex chromosomes. Now, Y-linked problems become W-linked (see, for example, Ogawa et al (1998), Yamada et al (2004), or Abe et al (2008)). For simplicity in notation, throughout this paper only the XX/XY sex determination system will be referred to, although the development and the results are equally valid for the ZZ/ZW system.…”
Section: Introductionmentioning
confidence: 99%